2007
DOI: 10.1080/10888430701344306
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Is Important for Some, but Not All Reading Skills

Abstract: Although there is evidence for a close link between the development of oral vocabulary and reading comprehension, less clear is whether oral vocabulary skills relate to the development of word-level reading skills. This study investigated vocabulary and literacy in 81 children of 8-10 years. In regression analyses, vocabulary accounted for unique variance in exception word reading and reading comprehension, but not text reading accuracy, decoding and regular word reading. Consistent with these data, children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
266
4
17

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 358 publications
(328 citation statements)
references
References 31 publications
41
266
4
17
Order By: Relevance
“…The evidence shows that they are, even during tasks that do not require meaning to be accessed, such as reading aloud/silently and lexical decision (judging whether a letter string is a word). Relative to reading pseudowords In both a meta-analysis and an empirical study, Taylor et al (2013;2014a) Semantic dementia patients are more likely to correctly read an exception word aloud if they still know the meaning of that word (Graham, Hodges, & Patterson, 1994), mirroring results in the developmental literature (Ricketts et al, 2007). Large scale studies of semantic dementia have shown a strong link between the degree of the exception word reading deficit and the severity of semantic impairment on tasks that do not require reading (e.g., picture naming, spoken word-to-picture matching; Woollams et al, 2007).…”
Section: Neuroimagingmentioning
confidence: 83%
See 1 more Smart Citation
“…The evidence shows that they are, even during tasks that do not require meaning to be accessed, such as reading aloud/silently and lexical decision (judging whether a letter string is a word). Relative to reading pseudowords In both a meta-analysis and an empirical study, Taylor et al (2013;2014a) Semantic dementia patients are more likely to correctly read an exception word aloud if they still know the meaning of that word (Graham, Hodges, & Patterson, 1994), mirroring results in the developmental literature (Ricketts et al, 2007). Large scale studies of semantic dementia have shown a strong link between the degree of the exception word reading deficit and the severity of semantic impairment on tasks that do not require reading (e.g., picture naming, spoken word-to-picture matching; Woollams et al, 2007).…”
Section: Neuroimagingmentioning
confidence: 83%
“…Developmental psychology can address the critical question: What role does semantics have in learning to read words? Longitudinal studies show that children's oral vocabulary knowledge (an index of semantic knowledge) is associated with word reading later on in development, particularly for exception words such as touch, where the ou is not pronounced in the usual way (as in couch; Nation & Snowling, 2004;Ricketts, Nation, & Bishop, 2007).…”
Section: Developmental Psychologymentioning
confidence: 99%
“…Although there is clear evidence of a general relationship between vocabulary knowledge and word reading (e.g. Nation & Snowling 2004;Ouellette 2006;Bowey & Rutherford 2007;Ricketts et al 2007), it is not clear whether semantic factors play a specific role in reading aloud. Evidence to date fails to find support for a semantic involvement (McKague et al 2001;Nation & Cocksey 2009a).…”
Section: Form -Meaning Connections and Learning To Readmentioning
confidence: 99%
“…Stanovich et al 1985). More generally, children who have weak semantic skills show relative weaknesses when reading aloud inconsistent or irregular words (Nation & Snowling 1998, 2004Ouellette 2006;Bowey & Rutherford 2007;Ricketts et al 2007), reminiscent of the relationship between word reading and semantic knowledge reported in semantic dementia.…”
Section: Form -Meaning Connections I: Is There a Role For Meaning In mentioning
confidence: 99%
“…Receptive vocabulary skills provide a foundation for the development of language, with vocabulary size being strongly associated with general intelligence, reading ability, reading comprehension, and school success (Ricketts, Nation, & Bishop, 2007). Findings from population based studies suggest 12-15% of 5-year old children have delays in receptive vocabulary skills (Harrison & McLeod, 2010;O'Callaghan, Williams, Andersen, Bor, & Najman, 1995).…”
Section: Introductionmentioning
confidence: 99%